Factors Affecting Consumer Satisfaction Using Mercure Bengkulu Hotel Services - Marleza, Yozi; Soleh, Ahmad; Abi, Yudi Irawan (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
Hotel is an accommodation service business in which there are elements of service, comfort, and lodging facilities needed for those who want lodging facilities for family and vacation purposes. This research was conducted at Mercure Bengkulu hotel, the sampling technique in this study used purposive sampling technique and data collection was carried out by distributing questionnaires to respondents. The questionnaire was distributed to 99 respondents at Mercure Bengkulu hotel. The analytical tools used are validity test, reliability test, multiple linear regression, and coefficient of determination using IBM SPSS version 25. Hypothesis testing using the T test and F test. This type of research is quantitative, which is research that analyzes data quantitatively and then interprets a conclusion. In this study, the data sources used were primary data and secondary data. The purpose of this study is to test and analyze whether there is an effect of service quality, price and facilities on customer satisfaction using services of Mercure Bengkulu hotel. Y = 1.134+0.227 X1+0.488 X2 +0.242 X3+Ɛ. The results showed that Service Quality (X1) has a regression coefficient of 0.227, meaning that if the quality of service increases by 1, customer satisfaction will increase by 0.227. The regression coefficient is positive between service quality and customer satisfaction. Price (X2) is 0.488, which means that if the price increases by 1, customer satisfaction will increase by 0.488. The regression coefficient is positive between price and customer satisfaction. Facility (X3) is 0.242, which means that if the facility increases by 1, customer satisfaction will increase by 0.242. The regression coefficient is positive between facilities and customer satisfaction.